2022
DOI: 10.1212/wnl.0000000000201201
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive-Driven Activities of Daily Living Impairment as a Predictor for Dementia in Parkinson Disease

Abstract: Objectives:One-third of Parkinson’s disease (PD) patients with mild cognitive impairment (PD-MCI) convert to dementia within a few years. Markers with a high prognostic value for dementia conversion are needed. Loss of everyday function primarily caused by cognitive dysfunction is the core criterion for the diagnosis of PD dementia, with an onset of more complex instrumental activities of daily living (IADL) dysfunction in the prodromal stage. This study evaluated the phenotype associated with cognitive IADL i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Cognitive function-associated sociodemographic variables, health behaviors, and health status variables were considered as covariates in our analysis, which have previously been reported to be associated with cognitive function among older adults (Durazzo et al, 2014;Koch et al, 2019;Lutsey et al, 2019;Zhang et al, 2020;Becker et al, 2022;Li et al, 2022;Nerobkova et al, 2022;Yu et al, 2022;Zhang et al, 2022;Bloomberg et al, 2023;Du et al, 2023). Sociodemographic variables included gender (male or female), age (60-69 years, 70-79 years, or ≥ 80 years), education level (illiterate/primary school, junior school, senior high school, or college or above), marital status (unmarried/divorced/widowed or married), living arrangement (alone or with others), household income (≤ 5,000, 5,001 -10,000, or > 10,000).…”
Section: Covariatesmentioning
confidence: 99%
“…Cognitive function-associated sociodemographic variables, health behaviors, and health status variables were considered as covariates in our analysis, which have previously been reported to be associated with cognitive function among older adults (Durazzo et al, 2014;Koch et al, 2019;Lutsey et al, 2019;Zhang et al, 2020;Becker et al, 2022;Li et al, 2022;Nerobkova et al, 2022;Yu et al, 2022;Zhang et al, 2022;Bloomberg et al, 2023;Du et al, 2023). Sociodemographic variables included gender (male or female), age (60-69 years, 70-79 years, or ≥ 80 years), education level (illiterate/primary school, junior school, senior high school, or college or above), marital status (unmarried/divorced/widowed or married), living arrangement (alone or with others), household income (≤ 5,000, 5,001 -10,000, or > 10,000).…”
Section: Covariatesmentioning
confidence: 99%
“…Our study showed that Parkinson patients with mild cognitive impairment and cognitive IADL impairment were at a higher risk of developing dementia. 1 Thus, we argue that the MoCA and the FAQ cognition score should be used together, not separately, to inform clinical trials.…”
mentioning
confidence: 99%
“…We appreciate the comment by Dr. Kasten on our article. 1 Regarding the question of whether the Montreal Cognitive Assessment (MoCA) and the cognition subscore of the Functional Activities Questionnaire (FAQ) correlate, we found weak-to-moderate correlations at baseline ( r = −0.28, p < 0.001, 95% CI −0.41 to −0.13) and follow-up ( r = −0.40, p < 0.001, 95% CI −0.53 to −0.26). However, it is important to keep in mind that the FAQ items comprising the cognition score were originally chosen based on correlations with the MoCA.…”
mentioning
confidence: 99%
“…An even steeper decline in ADLs can be expected in people at risk of developing neurodegenerative or other types of diseases (Buchman et al, 2009 ; Gill et al, 2013 ). Deficits in ADLs due to cognitive impairment are increasingly discussed as a risk factor for dementia in older age and neurodegenerative diseases (Verlinden et al, 2016 ; Becker et al, 2022 ; Jang et al, 2022 ; Ng et al, 2022 ), indicating a need for sensitive assessments, especially in mild stages of ADL difficulty. ADLs are affected by multiple factors such as physical fitness, cognitive ability, and mental health (Cahn et al, 1998 ; Tam et al, 2008 ; Christensen et al, 2013 ).…”
mentioning
confidence: 99%